Analisis Wacana Kritis Norman Fairclough atas Wacana Kepemimpinan dalam Tafsir al-Manār Karya Muḥammad ‘Abduh dan Rasyīd Ridhā - Roja Lukmanul Khovid (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
In Islam leaders are defined by various terms such as Khalifah an imam, and must have a character that is respected, fair, wisw, and honest. Leader must also pay attention to the norms, values, of society, and the development of increasingly advanced times, prioritizing profesionalism and extensive knowledge. The challenges faced by leades today include proverty, unemployment and crime, which ruquire leaders to have a fair attitude and high morals. This study aims to discuss leadership according to Rasyid Ridha and Muhammad Abduh in tafsir al-Manār . This research method is descriptive qualitative research, with the method of utilizing document that use library research techniques, namely by using data sourced from books and previous studies related to the discussion. The formulation of the problem in this study, first, How is the critical discourse analysis of leadership in the Egyptian local and global contexts. Second, the interpretation of leadership in tafsir al-Manār. Answering the formulation of the problem, the researcher got the following conclusions: (1) the discourse of leadership in tafsir al-Manār is the irregularity of the state of the local government of egypt at that time. Muhammad Abduh and Rasyid Ridha argued that leaders must create a harmonious, participatory, and transparet environment, as well as strengthen the sense of rensponbility and unity among the people. (2) The discourse of democratic leadership in the solution to the problem of interpretation. In explaining leadership, Rasyid Ridha begins by discussing the khalifah. In the following discussion, there arematters related to leadership and leaders. Such as, how to be a leader, the principles that must be held to be a leader, and what are the obligations and rights of a leader.